2021
DOI: 10.47552/ijam.v12i3.2070
|View full text |Cite
|
Sign up to set email alerts
|

Abhava pratinidhi dravya: A Comparative Phytochemical Study of Bharangi and Kantakari

Abstract: Abhava pratinidhi dravya excites the scientific curiosity concerning the Ayurvedic principles behind selection of the substitute drug. Present study had reported a comparative phytochemical study of one such Ayurvedic substitution pair: Solanum surattense Burm.f., a substitute for Clerodendrum serratum L. The study was conducted to understand the logic behind the Abhava pratinidhi dravya (Drug substitution). The strategy was to scrutinize and compare their Ayurvedic properties by literary studies and test the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, it has been observed that in South Indian Pharmacies, the root and root nodules of Pygmacopremna herbacea were used as Bhāraṅgī in their preparations (K. Vasudevan Nair et.al 1982) 5 . In a study conducted on the four Indian market samples of Bhāraṅgī, it was found that all samples were adulterated and none of the market sample was found as genuine drug Clerodendrum serratum 3,4,9 . Another study showed that the roots of Bhāraṅgī were adulterated with the stem of Clerodendrum serratum, mostly in South Indian markets 10,11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been observed that in South Indian Pharmacies, the root and root nodules of Pygmacopremna herbacea were used as Bhāraṅgī in their preparations (K. Vasudevan Nair et.al 1982) 5 . In a study conducted on the four Indian market samples of Bhāraṅgī, it was found that all samples were adulterated and none of the market sample was found as genuine drug Clerodendrum serratum 3,4,9 . Another study showed that the roots of Bhāraṅgī were adulterated with the stem of Clerodendrum serratum, mostly in South Indian markets 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted on the four Indian market samples of Bhāraṅgī, it was found that all samples were adulterated and none of the market sample was found as genuine drug Clerodendrum serratum 3,4,9 . Another study showed that the roots of Bhāraṅgī were adulterated with the stem of Clerodendrum serratum, mostly in South Indian markets 10,11 . Eventually there were no particular studies conducted on Bhāraṅgī in Kerala markets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation